Construction factors influencing beef demand index results - Strevell, Alex (Kansas State University, 2014)
Demand indices are used by many industries as a measurement tool to track changes and make yearly comparisons. Many different sources use demand indices to track the demand for beef. Indexes are an important tool to help better understand why demand shifts the way that it does and help strategically plan for the future of the industry. There are a wide variety of beef demand indices out in academia and many are constructed in different ways. This study advances the literature by testing which factors of index construction effect the results the greatest. This study tested four separate factors in the construction of demand indices. These iterations are as follows, changes in retail price data, changes in elasticities chosen, changes in export data, and changes in construction in terms of quantities instead of prices. Changes in retail price data do not appear to be statistically different. All estimates in this study where elasticities were changed appear to be different statistically, however the level of concern with this finding may be minimal due to the small increments of change in magnitudes of difference between indices. Results from omitting export data does appear to result in statistically different indices, but again the level of concern with the difference may be small. Finally, index construction in terms of prices versus construction in terms of quantities does not appear to have statistically different results, as the indices in this comparison move similarly. For all practical purposes in industry, it does not appear to matter which index is chosen for comparisons, as long as one remains consistent with which index is chosen for comparisons.
Keywords: demand index; Agriculture, General (0473)